Pengaruh Perhatian Orang Tua terhadap Hasil Belajar Pendidikan Agama Islam (PAI) Siswa SD Islam Khaira Ummah Kota Padang - Ainan Safika; Rini Rahman (Journal on Education, 2023)
This study aims to determine the effect of parental attention on PAI learning outcomes for fifth grade students at SD Islam Khaira Ummah which is located at Jl. Pagai Ikur Koto, Koto Panjang, Ikur Koto, Kec. Koto Tangah, P`adang City, West Sumatra Province. The research method used is a quantitative research method. The population in this study were fifth grade students at SD Islam Khaira Ummah. The research sampling technique uses the slovin formula. Data collection was carried out using a questionnaire. The data analysis technique used is the Pearson product moment correlation formula. The results showed that the t value of variable X was 3.080 and the t table value was 2.005 (3.080 > 2.005) and for the significance value of variable X and Y was 0.003 <0.05. And from the F test, the calculated F value of variable X is 9.485 and the F table value is 4.023 (9.485 > 4.023) and for the significance value of variable X and Y is 0.003 <0.05. So it was concluded that partially or simultaneously there was a significant influence between parents' attention to the learning outcomes of class V SD Islam Khaira Ummah.